Efficacy of Lactic Acid Bacteria Probiotics on Feed Efficiency and Carcass Weight in Kampung Unggul Balitbangtan (KUB) Chicken - Berlina, Cyrcilia Relita; Hidanah, Sri; Al Arif, Muhammad Anam; Luqman, Epy Muhammad; Yuniarti, Wiwik Misaco; Mufasirin, Mufasirin (Universitas Airlangga, 2023)
This study aimed to determine the effect of lactic acid bacteria probiotics on the performance of Kampung Unggul Balitbangtan (KUB) chicken. A total of 48 KUB chickens aged 2 weeks were randomized into 4 treatments and each treatment consisted of 12 chickens. This study was conducted for 8 weeks. This study used 4 different treatments including (P0) not using probiotics, (P1) using probiotics of 1 mL/L drinking water, (P2) using probiotics of 2 mL/L drinking water, and (P3) using probiotics of 3 mL/L drinking water. The data were analyzed using ANOVA continued with Duncan's Multiple distance test. As a result, reported that the data had a significant difference in the increase in feed efficiency and carcass weight. In conclusion, the administration of probiotics of 3 mL/L of drinking water can increase feed efficiency and carcass weight in KUB chickens.